Biochemical characterization of the mitochondrial tRNA(Ser(UCN)) T7511C mutation associated with nonsyndromic deafness - Li, Xiaoming (Oxford University Press, 2004)
We report here the biochemical characterization of the deafness-associated mitochondrial tRNA(Ser(UCN)) T7511C mutation, in conjunction with homoplasmic ND1 T3308C and tRNA(Ala) T5655C mutations using cybrids constructed by transferring mitochondria from lymphoblastoid cell lines derived from an African family into human mtDNA-less (ρ°) cells. Three cybrids derived from an affected matrilineal relative carrying the homoplasmic T7511C mutation, exhibited ∼75% decrease in the tRNA(Ser(UCN)) level, compared with three control cybrids. This amount of reduction in the tRNA(Ser(UCN)) level is below a proposed threshold to support a normal rate of mitochondrial protein synthesis in lymphoblastoid cell lines. This defect is likely a primary contributor to ∼52% reduction in the rate of mitochondrial protein synthesis and marked defects in respiration and growth properties in galactose-containing medium. Interestingly, the T5655C mutation produces ∼50% reduction in the tRNA(Ala) level in mutant cells. Strikingly, the T3308C mutation causes a significant decrease both in the amount of ND1 mRNA and co-transcribed tRNA(Leu(UUR)) in mutant cells. Thus, mitochondrial dysfunctions caused by the T5655C and T3308C mutations may modulate the phenotypic manifestation of the T7511C mutation. These observations imply that a combination of the T7511C mutation with two mtDNA mutations accounts for the high penetrance of deafness in this family.